Археологічні дослідження Острога доби князів Острозьких - Прищепа, Б.А. (Археологія, 2016)
Проаналізовано археологічні джерела з розкопок м. Острог у 2004—2013 рр. Вони надають важливу інформацію про характер забудови досліджених ділянок у різні історичні періоди, дозволяють поточнити історичну топографію замку князів Острозьких. In the 20th century, archeological collections from Ostroh area were formed as a result of small archaeological prospecting and occasional findings. Archeological research of the city in 2004—2013 allowed expanding significantly the source base for the study of the early stages of the settlement’s development. New materials were discovered to characterize various aspects of city life in the period of Ostrohski princes. Excavations were held within the territory of 1100 m² in different parts of Ostroh: in the castle area, in the town, and in the suburbs. The exploration included accommodation and utility buildings and the cemetery near the St. Nicholas Church; the author also specified the location of the northern part of suburbs fortifications; found out the remains of Lutsk Street which joined the market square and the Lutsk gate. In the northern part of the suburbs, the author discovered the section of the town’s defensive wall of Kyiv Rus period. This wall was used to construct the suburbs defensive line in the period of Ostrohski princes. Accommodation buildings of the 15th—17th centuries were on the surface, some of them had a square foundation pit (subterranean room) with an area from 9,0 to 30 m². Cellars, utility buildings and pits were explored near accommodation buildings. The collections of archeological findings of the period from the 14th to the 17th centuries include objects made of clay, metals, stone, bone, and glass. The 14th century assemblages were found only near the St. Nicholas Church and at 3, Nezalezhnist Avenue. Cultural layers and objects of the 15th and the beginning of the 16th centuries were found at all sections of archаeological exploration (with the exception of New Town). The cultural layer and objects of the second half of the 16th and the first half of the 17th centuries contained the largest number of archeological findings. В ХХ в. археологические коллекции с территории Острога были сформированы во время небольших разведочных работ и за счет поступлений случайных находок. Осуществленные в 2004—2013 гг. археологические исследования города позволили значительно расширить круг источников для изучения ранних этапов развития поселения. Интересные материалы получены для характеристики разных сторон жизни города времён князей Острожских. Раскопки проведены на площади 1100 м² в разных частях Острога: на территории замка, в городе и в предместьях. Исследованы жилые и хозяйственные постройки, кладбище возле Николаевской церкви, уточнено место расположения северного участка укреплений пригородка, выявлены следы улицы Луцкой, которая соединяла площадь Рынок и Луцкие ворота. У северного края пригородка открыт участок оборонного вала окольного города времен Киевской Руси. В эпоху князей Острожских этот вал был использован для сооружения оборонной линии пригородка. Жилища ХV—ХVІІ вв. были наземными, некоторые имели также четырехугольный котлован (подклеть) площадью от 9,0 до 30 м² . Рядом с жилищами исследованы погреба, хозяйственные постройки и ямы. Сформированные коллекции вещевых находок ХІV—ХVІІ вв. включают изделия из глины, металлов, камня, кости, стекла. Комплексы ХІV в. найдены возле Николаевской церкви и на проспекте Независимости, 3. Культурные слои и объекты ХV — начала ХVІ в. исследованы на всех участках, где были проведены раскопки (за исключением Нового города). Наиболее насыщенными находками оказались культурный слой и объекты второй половины ХVІ — первой половины ХVІІ в.